Global systematic map of research on bats in agricultural systems - Xavier, Bruna Silva; Rainho, Ana; Santos, Ana M. C.; Vieira, Marcus Vinícius; Carvalho, William Douglas (Frontiers in Ecology and Evolution, 2023)
Introduction The conversion of natural habitats to agricultural systems is one of the main global threats to bats. Here, we aimed to develop a systematic mapping to identify publication trends and research gaps in studying bats and agricultural systems. Methods We reviewed 309 studies published between 1990 and 2021 that sampled bats in agricultural systems or evaluated the effect of these systems on these animals. Results We found that most studies were conducted in the Palearctic and Neotropical regions (55.3%) and forest biomes (66.0%). Grassland-cropland systems (50.2%) and forest plantations that do not require cutting during the extraction of their products (47.9%) were more studied than forest plantations that require cutting (19.7%). Additionally, acoustic recordings (41.1%) and mist nets (34.3%) were the primary sampling methods used, with few studies combining these methods (7.1%). Also, most studies were conducted on a local scale (77.7%). The number of landscape-scale studies was smaller (34.3%) and concentrated in the Palearctic region (39.6%). Most studies assessed how agricultural systems affect biodiversity (62.1%). However, the phylogenetic and functional dimensions and b-diversity were little explored, with 2.5% and 23.3% of the biodiversity studies, respectively. Of the proposed mitigation measures, the most cited was including natural/semi-natural/potential bat habitats in cultivated landscapes (59.5%). Discussion In summary, our findings highlight the need for attention to the Afrotropic and Indo-Malaysia regions; predominantly non-forested biomes; plantations that require cutting during the extraction of their products; combined use of different sampling methods, as well as other methods as telemetry; use of multiple biodiversity descriptors and others biological descriptors, such as ecological services; landscape-scale studies and the role of conservation policies in promoting their conservation and raising awareness of their importance among producers and local communities. Filling these knowledge gaps is necessary to understand the factors influencing bat survival in cultivated landscapes. This is the only way to develop management and conservation strategies in these landscapes.